Adult‐born dentate neurons are recruited in both spatial memory encoding and retrieval. Issue 11 (13th May 2015) - Tronel, Sophie; Charrier, Vanessa; Sage, Cyrille; Maitre, Marlene; Leste‐Lasserre, Thierry; Abrous, Djoher N.
ABSTRACT Adult neurogenesis occurs in the dentate gyrus (DG) of the hippocampus, which is a key structure in learning and memory. Adult‐generated granule cells have been shown to play a role in spatial memory processes such as acquisition or retrieval, in particular during an immature stage when they exhibit a period of increased plasticity. Here, we demonstrate that immature and mature neurons born in the DG of adult rats are similarly activated in spatial memory processes. By imaging the activation of these two different neuron generations in the same rat and by using the immediate early gene Zif268, we show that these neurons are involved in both spatial memory acquisition and retrieval. These results demonstrate that adult‐generated granule cells are involved in memory beyond their immaturity stage. © 2015 Wiley Periodicals, Inc.